2018
DOI: 10.3168/jds.2017-14308
|View full text |Cite
|
Sign up to set email alerts
|

Low colostrum yield in Jersey cattle and potential risk factors

Abstract: Consumption of an adequate volume of high-quality colostrum is vital to a dairy calf's ability to survive and become a productive herd member. However, some dairy herds have reported a deficiency of colostrum production, which ranges from a low volume to no colostrum produced, by cows during fall and winter. Little information regarding this phenomenon exists. The purpose of this study was to characterize the syndrome and identify potential risk factors for low colostrum yield. A 2,500-cow Jersey dairy farm wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 21 publications
(27 reference statements)
5
26
1
9
Order By: Relevance
“…In a year-long study of a 2500-cow Jersey dairy in Texas, colostrum yield was highest in June but declined during the fall and winter months. 59 A low-temperature humidity index and a shortened photoperiod 1 month before and at calving were both highly correlated with reduced colostrum yield. The investigators hypothesized that shortened photoperiod may reduce colostrum production because of its impact on melatonin and prolactin, hormones known to be involved with colostrogenesis.…”
Section: Season Of Calvingmentioning
confidence: 95%
See 2 more Smart Citations
“…In a year-long study of a 2500-cow Jersey dairy in Texas, colostrum yield was highest in June but declined during the fall and winter months. 59 A low-temperature humidity index and a shortened photoperiod 1 month before and at calving were both highly correlated with reduced colostrum yield. The investigators hypothesized that shortened photoperiod may reduce colostrum production because of its impact on melatonin and prolactin, hormones known to be involved with colostrogenesis.…”
Section: Season Of Calvingmentioning
confidence: 95%
“…60 Producers should adopt heat-abatement strategies for prepartum cows and heifers and are advised to bank frozen colostrum to meet needs during low colostrum production months. 59…”
Section: Season Of Calvingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been observed that the Jersey breed will produce very little colostrum during the winter months in the northern hemisphere. 8 The effect was observed more for cows with greater than one parity and appears to be correlated with photoperiod (day-length).…”
Section: Breed and Parity Effectsmentioning
confidence: 94%
“…En cuanto al estado nutricional de la vaca en el periodo pre-parto, no se ha hallado relación entre las restricciones nutricionales y algún efecto negativo sobre el calostro, puesto que, en dietas que no excedían los requerimientos energéticos de las vacas, se hallaron mayores concentraciones de inmunoglobulinas que en dietas con exceso de energía y no se encontraron diferencias significativas en la producción de calostro entre ambos casos (Mann et al, 2016). En lo que respecta a la duración del periodo seco y el volumen producido en la primera lactancia, se reporta que entre más corto sea el periodo seco, más baja puede ser la producción de calostro (Gavin et al, 2018).…”
Section: Calostrounclassified